Electrolytes Status in Different Type of Acute Stroke Patients and Their Correlation with Some Common Clinical Presentation - Siddiqui, Mahmudur Rahman; Islam, Quazi Tarikul; Haque, Md Azharul; Iqbal, Md Jabed; Hossain, Ahmed; Rahman, Yousuf Ur; Mahbub, Md Shahriar; Sazzad, Asif Alam (Journal of Medicine, 2012)
Background: In our country, there are many studies on stroke, its associated conditions and their effect on stroke patients outcome, but a few studies on electrolytes status in stroke patients have been done in our country, even outside. Method: A total number of 100 randomly selected, clinically and CT proven acute stroke patients were studied at medicine units of Dhaka Medical College Hospital. Electrolytes status in different type of acute stroke patients and their association with some common clinical presentation were identified and correlated. Result: Out of 100 patients, 29% were in between 51-60 years age group & 72% were male and 28% were female patients. Majority 53% patients had Ischaemic stroke, 45% Intracerebral haemorrhage (ICH) and only 2% had Subarachnoid haemorrhage (SAH). 53% of total acute stroke patient had dyselectrolytaemia. Among 100 acute stroke patients, 66.66% haemorrhagic stroke and 28.30% ischaemic stroke patients had headache (p<0.05). 70.66% haemorrhagic and 30.23% ischaemic stroke patients had vomiting (p<0.05). 53% of total acute stroke patient had dyselectrolytaemia. Among 100 acute stroke patient 49 (49%) presented with vomiting from which 73.46% had dyselectrolytaemia (p<0.01). 54 (54%) presented with headache from which 74.07% had dyselectrolytaemia (p<0.001). 62.22% of haemorrhagic stroke (p<0.05) & 43.39% of ischaemic stroke (p>0.05) patients had dyselectrolytaemia. Total 36% of all stroke patients had serum sodium imbalance & 31% had serum potassium imbalance. In haemorrhagic stroke & ischaemic stroke patients, hyponatraemia (17% & 13%), hypernatraemia (1% & 3%), hypokalaemia (19% & 11%), hyperkalaemia (0% & 1%), hypochloraemia (9% & 6%) respectively. Conclusion: In haemorrhagic stroke, the incidence of electrolytes imbalance was more than ischaemic stroke and which were mostly hyponatraemia and hypokalaemia. DOI: http://dx.doi.org/10.3329/jom.v13i2.12740 J Medicine 2012; 13 : 133-137